Teaching composition as a social process - McComiskey, Bruce, 1963- (Utah State University Press, 2000)
Bruce McComiskey is a strong advocate of social approaches to teaching writing. However, he opposes composition teaching that relies on cultural theory for content, because it too often prejudges the ethical character of institutions and reverts unnecessarily to product-centered practices in the classroom.